27‐1: Study on the effect of controlling the pretitle angle using RM with multipolymerizable functional group. Issue 1 (29th May 2019) - Li, Qian; Zhang, Yu; Wei, Hongquan; Cui, Wei; Tseng, Te-Jen; Hsieh, Chung-Ching; Chiu, Chung-yi
Abstract : RM have played an integral role in the produce of generating the pretilt angle. In this study, we use Reactive Mesogen with multipolymerizable functional group and adopt UV curing process to investigate the pretilt alignment of liquid crystal, and normal RM (RM with two polymerizable functional group) as a reference. The pretilt angle formation and reliability performance of different RM are discussed.